SOLO TAXONOMY AS INSTRUMENT FOR STUDENT ESSAY EVALUATION - Targamadzė, Vilija; Nauckūnaitė, Zita (Acta Paedagogica Vilnensia, 2009)
This article analyses the problem of the student essay evaluation, which currently is very topical in Lithuania. The starting point for the article is the analysis of the student essays written during the state final examination of the Lithuanian (native) language 2008. It reveals the difficulties encountered when evaluating reasoning essays and interpretations of extracts from literary writings, with particular focus on the evaluation of the essay content and structure. The article centres on the question if the SOLO taxonomy is a suitable instrument for the evaluation of student essays and aims at presenting SOLO as a possible essay evaluation instrument. The subject of the study is the SOLO taxonomy in respect of the essay evaluation. The simulation and the analysis of the academic literature and research were chosen as study methods. The article also discusses Bloom’s taxonomy and the New taxonomy as well as presents the interconnection of the SOLO taxonomy and Bloom’s taxonomy. It also lists the levels of the SOLO taxonomy along with their corresponding examples from the student essays, which proves the suitability of the SOLO taxonomy for the evaluation of those essays. The conclusion stresses the potential of the SOLO taxonomy for the encouragement of a holistic attitude towards the process of education.
Keywords: SOLO taxonomy; Bloom’s taxonomy; New taxonomy; student essays; evaluation